Effects of rodents’ behaviours on leptospirosis spread : an individual-based modeling approach - Jia Wen, Chong; Wei King, Tiong; Jane, Labadin; Phang, Piau (Lviv Polytechnic National University, 2022)
Leptospirosis is a zoonotic disease common in tropical and subtropical regions. This infectious disease is endemic in Sarawak, Malaysia. In recent years, the threat of leptospirosis is on an increasing trend in Sarawak since 2010. The traditional compartmental models assume that the population is homogeneous and shares the same characteristics and behaviours. However, each individual in the population has different and unique behaviour in the real world. Thus, this paper aims to model the leptospirosis spread by adopting the individual-based modeling approach to address the heterogeneity that affects the transmission of the disease. Rodents’ behaviours such as active period duration and movement range are incorporated into the model. From the sensitivity analyses, the results show that the movement range of the rodents has a significant impact on the spread of the disease compared to the active period duration. The comparison between simulation results and the actual prevalence data in Sarawak is performed to validate the model. Through regression analysis, the correlations of determination for three outbreaks in Sarawak for the year 2017 are more than 90%. In addition, the normal probability plots for three outbreaks indicate the points follow the line well and are normally distributed. This shows that the proposed individual-based model can predict leptospirosis transmission.